Calculation of the minimum reflux ratio for various cases of rectification of binary mixtures - M. K. Zakharov; A. A. Shvets; A. A. Boichuk (Тонкие химические технологии, 2015)
The methods of calculation of the minimum reflux ratio for actual binary mixtures with the possibility of formation of the pinch modes was considered. It is proved that in the presence of the pinch mode in the product-concentrating column the value of the minimum reflux ratio doesn't depend on the aggregate state of the initial mixture. In the case of pinch mode in the stripping column a formula for calculating the minimum reflux ratio taking into account the energy level of the initial mixture is obtained.